Laporan Kasus: Katarak Akibat Kerja pada Buruh Perkebunan Kelapa Sawit - Sugiharto Sugiharto; Dewi Yunia Fitriani (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2022)
Introduction: Cataract in workers need to be distinguished whether it is an occupational disease or not. Palm oil plantation workers are one of the high-risk jobs for potential hazards in the workplace that have an impact on health, one of which is cataract. Case report: A 38-year-old male oil palm plantation worker with complaints of blurred eyes since 1.5 years ago, sensitivity with lights and glare, and clouded. He was exposed ultraviolet (UV) rays 5 hours every day for 18 years without UV protective eyewear. To on examination revealed visual acuity in the right eye was 6/60 and the left eye was 6/9, both posterior subcapsular lenses opacities, vitreous papillae on the right were blurred.Discussion: Occupational cataract in oil palm plantation workers can be caused by prolonged exposure of UV rays, without wearing UV protective eyewear. The examination revealed decreased vision, posterior subcapsular lens opacities and blurred papillae. Determination of occupational cataract refers to the Seven Steps Occupational Diagnosis method issued by PERDOKI (Indonesian Association of Occupational Medicine Specialists).Conclusion: Occupational cataract can be diagnosed by the Seven Steps Occupational Diagnosis method and prevented by administrative controls and the use of UV protective eyewear.